2009
DOI: 10.1017/s1368980009005928
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and use of iron and iron-alloy cooking pots: implications for anaemia control programmes

Abstract: Objective: To evaluate the acceptability of iron and iron-alloy cooking pots prior to an intervention trial and to investigate factors affecting retention and use. Design: Pre-trial research was conducted on five types of iron and iron-alloy pots using focus group discussions and a laboratory evaluation of Fe transfer during cooking was undertaken. Usage and retention during the subsequent intervention trial were investigated using focus group discussions and market monitoring. Setting: Three refugee camps in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…However, studies in refugee contexts have indicated that MNP is not always well accepted and that adherence can be low (16) . When introducing any nutrition or health intervention, including within refugee contexts, the issues of acceptability and adherence in the local context should be key considerations (17) . Therefore, prior to the initiation of a blanket supplementary feeding programme to reduce anaemia and stunting within the refugee camps in Algeria, a field-based study was designed and conducted.…”
mentioning
confidence: 99%
“…However, studies in refugee contexts have indicated that MNP is not always well accepted and that adherence can be low (16) . When introducing any nutrition or health intervention, including within refugee contexts, the issues of acceptability and adherence in the local context should be key considerations (17) . Therefore, prior to the initiation of a blanket supplementary feeding programme to reduce anaemia and stunting within the refugee camps in Algeria, a field-based study was designed and conducted.…”
mentioning
confidence: 99%
“…[10] Geerligs et al [11] Kollipara and Brittin. [12] Liu et al [13] Park and Brittin [14] Tripp et al [15] in their studies, where iron was leached from iron cooking equipment in a greater quantity. Studies by Borigato and Martinez.…”
Section: Discussionmentioning
confidence: 99%
“…Cast-iron pots were reported to be heavy, rust easily, and required more attention for cooking due being prone to higher cooking temperatures [75]. In one study it was found that participants were selling the cast iron pots in the market in order to supplement low family incomes [78]. On the other hand, cast iron pots required less wood for stoves since cooking times were faster, and the pots were considered to be very durable [75].…”
Section: Cast Iron Potsmentioning
confidence: 99%